WEICIBI (Weiji Chinese Braille): Website Development to Improve Simple Conversational Text Writing Skills in Chinese Braille for Totally-Blind Students - Pahlawaty, Neddyana; Aprilia, Imas Diana; Sunardi, Sunardi (Journal of ICSAR, 2024)
The use of website as an accessible media can be an alternative in learning to write Chinese text. The purpose of this research is to develop an accessible website which can improve the skill of writing simple conversational Chinese texts writing skills for totally-blind class XI students. The research method used is RnD with ADDIE model. The data were collected through interviews, observations, documentation studies, and tests. This research produced a website that was developed based on the analysis of students' ability profiles and the application of MiBee Braille application. Weicibi can improve students' writing skills as shown by an increase in the mean level of phase A1 of 29.25, phase B of 61, and phase A2 of 83. Weicibi has learning and translator features supported by video tutorials. The conclusion is that the Weicibi developed is feasible to use and be effective in improving the writing skills of totally-blind students.